2018
DOI: 10.1002/sia.6465
|View full text |Cite
|
Sign up to set email alerts
|

Surface analysis of iron and steel nanopowder

Abstract: High sinter density is desired in powder metallurgy components as the requirement for performance is increasing day‐by‐day. One of the promising ways to achieve improved densification during sintering is through the addition of nanopowder to the conventional micrometer sized metal powder. It is well known that the surface chemistry of the powder has a decisive effect on sintering and consequently the properties of the components produced. Extensive research has hence been conducted to elucidate the surface che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…A surface analysis of both the nanopowder and the reduction of surface oxide has been discussed elsewhere. [9] The powder blends and the lubricant were compacted at compaction pressures of 400, 600 and 800 MPa. Figure 2 shows the compressibility curves for the compacts of all the powder blends.…”
Section: A Materials and Compactionmentioning
confidence: 99%
See 1 more Smart Citation
“…A surface analysis of both the nanopowder and the reduction of surface oxide has been discussed elsewhere. [9] The powder blends and the lubricant were compacted at compaction pressures of 400, 600 and 800 MPa. Figure 2 shows the compressibility curves for the compacts of all the powder blends.…”
Section: A Materials and Compactionmentioning
confidence: 99%
“…As shown in the fractographs (Figure 8), nanopowder was sintered in the temperature range between 500°C and 700°C. As the sintering was conducted in a pure hydrogen atmosphere, which reduces iron oxide in the range of temperatures between 300°C and 500°C, [9] the oxide scale covering the nanoparticles was reduced. The oxide layer plays a crucial part in sintering, as sintering is a surface phenomenon.…”
Section: Influence Of Nanopowder Additionmentioning
confidence: 99%
“…In our previous study, it was seen that when such a metallic shoulder is observed, the scale thickness is generally 3 to 4 nm. 4 Zinc is considered to be an impurity and could be from the manufacturing process.…”
Section: Resultsmentioning
confidence: 99%
“…The present study aims to characterize the surface products of the carbon-coated iron nanopowder using X-ray photoelectron spectroscopy (XPS), Auger electron spectroscopy (AES), and high-resolution scanning electron microscopy (HR-SEM) and to correlate with the findings from thermogravimetric analysis. The oxide thickness determination for nanopowder has been studied before, 4 whereas this study emphasize on the changes that the nanopowder undergoes during the heating phase of the sintering from the perspective of surface chemistry.…”
mentioning
confidence: 99%
“…Iron nanopowder is hence used in the present research as an additive to improve the density of water-atomized iron powder compacts. The iron nanopowder was found to be covered with an oxide scale of 3 nm thick [7]. For the sintering process to be efficient, this surface oxide on the metal particle must at least in part be reduced.…”
Section: Introductionmentioning
confidence: 99%